Integrasi Nilai Islam Dalam Perumusan Misi Pendidikan Islam - Muhamad Geri Gunawan; Mulyawan Safwandy Nugraha (Peneliti.net, 2026)
This study aims to examine how Islamic values are integrated into the formulation of the vision, mission, and objectives of Islamic education, with a focus on four main aspects: tauhid, akhlak, ukhuwah, and amanah. This study uses a literature review method with a descriptive qualitative approach, through an analysis of Sinta and Scopus accredited journals, as well as relevant academic literature. The results show that tauhid serves as a transcendental foundation that affirms the orientation of Islamic education as a form of devotion to Allah SWT. Akhlak is an important pillar of character building, ukhuwah strengthens social solidarity, while amanah ensures institutional accountability and integrity. The integration of these four values has been proven to not only maintain spiritual identity, but also increase institutional legitimacy so that the vision and mission do not remain as administrative documents, but become strategic guidelines that are alive in educational practice. These findings complement previous studies that focused more on the curriculum aspect, while also confirming the theoretical contribution to the development of Islamic education management and the practical benefits for educational institutions in formulating a vision and mission that are relevant to global challenges, yet remain rooted in Islamic values.